(untitled) (Dhaka University Journal of Science, 2022)
A simple, rapid, and efficient spectrophotometric method was developed for the quantification of respirable crystalline silica (SiO2) in atmospheric particulate matter (PM). The PM samples were collected for 24 hours from two different locations at the University of Dhaka (Mukarram Hussain Khundker Building-MHK and Teacher Student Centre-TSC) using a low-volume air sampler from September to December 2021. The extraction of PM loaded filters followed by filtration resulted in a clear solution. Using UV-visible spectroscopy, the concentration of silica in the filtrate was evaluated by treating the filtrate with molybdate-3 reagent and an amino acid suspension. The average PM-bound silica concentrations at MHK and TSC were 7.72 and 33.86 μgm-3 respectively. Compared to MHK, the silica content in the ambient atmosphere of TSC was four times higher, owing to extensive metro-rail construction work at TSC. The contribution of silica to PM was 3.47% (Site 1) and 5.15% (Site 2). The Hazard Quotient (HQ) was used to characterize the non-cancer risk posed by respirable silica. TSC recorded a high value of 12.87 for the hazard quotient of respirable silica compared to 2.57 for MHK indicating that the exposed inhabitants may have adverse noncancer health impacts. Carcinogenic risk assessment of silica showed that 1 in 341 individuals at MHK and 1 in 78 individuals at TSC could get cancer in their lifetime. This is the first study that demonstrated the high level of PM-bound respirable silica severely degraded air quality as well as potential human health in Dhaka. Dhaka Univ. J. Sci. 70(2): 35-41, 2022 (July)